Georgian Hymnography - Nestan Sulava (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
The paper sheds light on several trends of the development of Georgian hymnography, schools and the history of its study: from the standpoint of form, theology, literary-historical, symbolic-imagery and ideological standpoints. Identified are hymnographic schools of Palestine and Sinai, Tao-klarjeti, Mt. Athos, Gelati, Shiomghvime, David Gareja and the Catholic sate of Mtkheta, in particular the theological-hymnographic schools of Anton the Catholicos, which determined the stages, level and trends of the development of hymnography in Georgia. Georgian hymnography was in close relations with that of Byzantium with its themes, world view and metaphorical system, hence it is conceptualized in the context of Byzantine hymnographic culture. The difference is shown between the musicality and poetics of Georgian and Byzantium hymn, manifested in the polyphony of Georgian song and the originality of the form of hymn. The outlines the prospects of research from a new point of view into the history and theory of Georgian and Byzantine hymnography.